Case Report: Concomitant Diagnosis of Plasma Cell Leukemia in Patient With JAK2 Positive Myeloproliferative Neoplasm - Kurian, Christine J.; Thomas, Colin; Houtmann, Sarah; Klumpp, Thomas; Binder, Adam Finn (Frontiers in Oncology, 2020)
Plasma cell dyscrasias and myeloproliferative neoplasms are hematologic malignancies arising from two distinct hematopoietic cell lineages. They rarely occur concomitantly. Here, we report a case of a patient with a recent diagnosis of a JAK2 V617F positive MPN who presented with a new diagnosis of plasma cell leukemia. The patient had presented to the hospital with a leukocytosis predominantly comprised of plasma cells, followed by work-up involving peripheral blood flow cytometry, FISH analysis and bone-marrow biopsy. FISH analysis was suggestive of a common progenitor cell for these distinct hematologic malignancies. To our knowledge, this case represents the first reported instance of a concomitant JAK2 positive MPN with primary plasma cell leukemia.